69‐2: Transparent Conductive Hybrid Cathode Structure for Top‐Emitting Organic Light‐Emitting Devices. Issue 1 (25th September 2020) - Quan, Wei; Wu, Chang-Yen; You, Juanjuan; Wang, Linlin; Song, Wenfeng; Shen, Yongqi; Luo, Chengyuan; Yu, Donghui; Bo, Bin; Sun, Li; Shih, Huai-Ting; Wu, Zhongyuan
Abstract : There is an increasing attention paid to improving transparent conductive electrodes for applications in highly transparent and large area displays. We optimized top‐emitting blue organic light‐emitting diodes (TE‐BOLEDs) using hybrid cathode consisting of a thermally evaporated Mg/Ag capped with IZO. The device of cd/A/CIEy which used the hybrid cathode improved by 20% more than that with the identical organic layers and conventional Mg/Ag cathode. Meanwhile the transparency increased by 13% and sheet resistance decreased by half. Balancing the device performance, transparency and resistivities, different hybrid cathode structure could meet various requirements.